Effect of Use of Management Accounting Systems on Competitive Advantages: Business Unit Performance as a Mediator (Study of MSMEs in Palembang City) - Delfi Panjaitan; Desy Lesmana; Mutiara Maimunah (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2018)
Micro, Small, and Medium Enterprises (MSMEs) are business units managed by community groups and families. SMEs has a strategic role in Indonesia economic development, because in addition to contributing to national economic growth it can also absorb large numbers of workers. However, micro, small and medium businesses have a low competitive advantage in the current era of globalization and technology. For this reason, MSMEs need resources that can be managed to win business competition in Indonesia. One of the most important resources managed in winning business competition is information resources. This study aims to prove the influence of the use of management accounting systems on competitive advantage, with business performance as a mediator. The data of this study were collected through a survey by distributing questionnaires. The sample in this study was MSMEs scale company in the city of Palembang using the purposive sampling method. Data analysis technique uses path analysis test. Based on data and research results it can be concluded that Business Unit Performance mediates the relationship between Management Accounting Systems and Competitive Advantages.